2011
DOI: 10.5038/1827-806x.40.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Minerals and speleothems of the József-hegy Cave (Budapest, Hungary)

Abstract: With the discovery of the József-hegy Cave, a cave of hydrothermal origin with an abundance of minerals unknown so far in Hungary came to light. Diversity and the frequency of the occurrence of crystals make this cave similar to the Lechuguilla Cave, even if the dimensions of the mineral precipitations and the passages do not compare in scale. The variety and mass of carbonates and sulphates are surprising. This paper describes the minerals and speleothems of the József-hegy Cave, their occurrence and genesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 2 publications
0
11
0
1
Order By: Relevance
“…(LEÉL-ŐSSY SZ. 1995, 1997a, b, 2005LEÉL-ŐSSY & SURÁNYI 2003;LEÉL-ŐSSY et al 2011) már műszeres anyagvizsgálatokat is végzett. NAGY S. (2008), ERŐSS (2010), POROS (2011), POROS et al (2012, GYŐRI et al (2011), valamint újabban VIRÁG et al (2011, 2013a és VÖRÖS et al (2013) további budai barlangok kép -ződményeit vizs gálta.…”
Section: A Budai Barlangok áSványvilágaunclassified
“…(LEÉL-ŐSSY SZ. 1995, 1997a, b, 2005LEÉL-ŐSSY & SURÁNYI 2003;LEÉL-ŐSSY et al 2011) már műszeres anyagvizsgálatokat is végzett. NAGY S. (2008), ERŐSS (2010), POROS (2011), POROS et al (2012, GYŐRI et al (2011), valamint újabban VIRÁG et al (2011, 2013a és VÖRÖS et al (2013) további budai barlangok kép -ződményeit vizs gálta.…”
Section: A Budai Barlangok áSványvilágaunclassified
“…To the list of 25 caves reported in Audra et al (2009), we have added La Baume Cave in France (reported in Davis, 2012), Odelsteinhöhle in Austria (Plan and De Waele, 2011), Cave of the Winds, Colorado, and Fort Stanton Cave, New Mexico, both reported in Davis (2012), Cueva de Villa Luz in Mexico (Hose, 2009), the Sima de la Higuera near Murcia in Spain (Gázquez and Calaforra, 2013), the cavelets of Glenwood Canyon, Colorado (Polyak et al, 2013), and the Santa Catalina Cave near Matanzas in Cuba, subject of this paper. Most of the caves in which folia have been reported are of thermal and/or hypogenic origin, such as Sima de la Higuera (Gázquez and Calaforra, 2013), Devil's Hole in Nevada (Kolesar and Riggs, 2004), Giusti cave in Tuscany, Italy (Piccini, 2000), and the Buda Hills caves (Takacsné Bolner, 1993;Leel-Ossy et al, 2011). However, this is not the rule, as folia have also been described from epigenic-cold caves, such as Hurricane Crawl Cave in California (Davis, 2012) and Odelsteinhöhle in Styria, Austria (Plan and De Waele, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…At certain locations the hot waters rising from depth are responsible for the precipitation of an abundant and diverse suite of carbonates and sulfates (gypsum, barite, and celestine), along with some exotic minerals (e.g., fluorite, quartz, etc. ; Dublyansky, 1995;Leél-Őssy et al, 2011). In contrast, in CPV the minerals are not deposited directly from deep-seated thermal groundwaters, but instead, they are a product of the interaction between mineralized warm brackish waters and the carbonate bedrock or preexisting minerals.…”
Section: Romanèchitementioning
confidence: 99%
“…Although less abundant and diverse when compared to the sulfuric acid caves, the mineralogy of thermal cavities has certain characteristics; among them, the presence of tabular barite and celestine crystals, as well as quartz, opal, or chalcedony that coat or even replace cave bedrock walls (Takácsné Bolner, 1989;Leél-Őssy et al, 2011).…”
Section: Geologic and Karst Settingsmentioning
confidence: 99%